Microelectrode arrays for applications in electrochemical analysis - Rehacek, Vlastimil; Hotovy, Ivan; Vojs, Marian (Univerzita Pardubice, 2012)
The greater availability of microlithographic techniques for the fabrication of electrochemical devices has led to a significant increase in the development of microelectrodes and microelectrode arrays of various geometries with their excellent electrochemical properties. This paper is focused on theoretical aspects of microelectrodes and microelectrode arrays with loosely and densely spaced electrodes, their fabrication processes and electrochemical characterization. In this review, our attention is focused on microdisc electrode arrays and interdigitated array electrodes. Finally, selected examples are presented of the application of microelectrode arrays in environmental analysis.
Keywords: microelectrode; microelectrode array; microdisc array; interdigitated array electrodes; mercury electrode; bismuth film electrode; diamond-like carbon; boron-doped diamond; voltammetric determination